Contemporary Bushman Art, Identity Politics and the Primitivism Discourse - Guenther, Mathias (Anthropologica, 2022)
In recent years artists from two San communities in Botswana and Namibia have been producing paintings and prints which have become sought after by Western collectors, as instances of African "primitive art." The art is produced in a context of intense identity politics, which in recent years have awakened the San politically and placed this hitherto passive ethnic minority on a course of political action. The art is especially relevant to the issues of identity and self-representation, and holds the potential for exposing and displacing the colonialist, and still cherished, icon of the timeless hunter gatherer of the far-away veld. The paper will show how this potential is thwarted by the Western perspective on the art, which, blind to its decolonizing images, sees it as reinforcing, rather than challenging, primordialist stereotypes.